Pengaruh Promosi Penjualan Dan Gender Terhadap Perilaku Impulse Buying Pada E-Commerce Shopee - Avrilia Gusti Purwaningsih; Nurhadi Nurhadi (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2021)
This study aims to analyze the effect of sales promotion on impulse buying on e-commerce Shopee with gender as a moderating variable in the form of a dummy variable. The sample of this study was 233 respondents with multiple linear regression analysis techniques and chi square. The result is that coupons have a negative and significant effect on impulse buying. variables Rebates, bonus pack, free premium gift, and event have a positive and significant effect on impulse buying. The variables price-off deals, loyalty program, and gender did not have a significant effect on impulse buying. test results Chi square also support that gender has no effect on impulse buying